The neurobiological underpinning of the social cognition impairments in patients with spinocerebellar ataxia type 2. (May 2021) - Clausi, Silvia; Olivito, Giusy; Siciliano, Libera; Lupo, Michela; Bozzali, Marco; Masciullo, Marcella; Molinari, Marco; Romano, Silvia; Leggio, Maria
Abstract: Clinical studies described emotional and social behaviour alterations in patients with cerebellar diseases, proposing a role of specific cerebello-cerebral circuits in social cognition. However, for a long time these difficulties were underestimated, and no studies have addressed the correlation between social cognition deficits and topography of the cerebellar damage. The present study aims to investigate the social cognition impairment and the neuroanatomical alterations in patients with spinocerebellar ataxia type 2 (SCA2) and to analyze their relationship. To this purpose a social cognition battery composed by three tests, and a MRI protocol were administered to 13 SCA2 patients and 26 healthy subjects. The pattern of gray matter (GM) atrophy was analyzed by voxel-based morphometry, and the GM volumes of each altered area were correlated with the behavioral scores to investigate anatomo-functional relationships. In addition, we investigated the relationship between social deficits and damage to the cerebellar peduncles using DTI diffusivity indices. Our patients showed impairment of the immediate perceptual component of the mental state recognition (i.e., to recognize feelings and thoughts from the eyes expression), and difficulties in anger attribution, and in the understanding of false or mistaken beliefs. They showed a pattern of GM reduction in cerebellar regions, including lobules IX and VIIIb and Crus II, all of which are involved in specific components of the mentalizing process. Interestingly, the behavioral performance, in which SCA2 patients showed impairments compared to controls, correlated with the degree of cerebellar GM reduction and with the presence of microstructural abnormalities in the cerebellar peduncles. The present study provides the first characterization of the social cognition deficits in a homogenous cohort SCA2 patients and demonstrates that alterations in specific cerebellar regions should represent the neurobiological underpinning of their social behavior difficulties. Our results offer a new point of view in considering these aspects in the clinical practice.